A cross-sectional study of the development of lateral preference in ice hockey - Dubeau, C.-A.; Thibault, N.; Grondin, S. (Research Quarterly for Exercise and Sport, 2025)
In ice hockey, players choose between one of only two ways to hold a stick, which reflects what is referred to as one`s lateral preference in ice hockey. What determines this preference remains unknown. While handedness appears to be an important determinant of ice hockey`s lateral preference, proportions demonstrate it cannot be the only influencing factor. The aim of the study was (1) to identify when ice hockey`s lateral preference is determined in one`s development and (2) empirically identify some of its determinant. The sample consisted of 106 children aged three to six, who were asked to perform a stick-handling task. The goal was to test whether their instinctive lateral preference aligned with their optimal lateral preference (i.e. the one in which they performed best), and whether this alignment was more frequent in older children. Neither chi-square nor segmented regression analyses revealed such alignment. Still, the present results suggest that ice hockey`s lateral preference is likely determined around 5 years old. Also, parents were asked to answer a home-made questionnaire, which aimed to identify the potential determinant of their children`s lateral preference in ice hockey. Parents identified "children`s own choice" and parental observation as the main determinants. These two factors thus join handedness (which received further support in the present study) as potential determinants of ice hockey`s lateral preference.